Creation of Contemporary Batik with Brush Stroke Motifs Using Layering Technique - Sekar Fardhani, Ahda Yunia; Katresna, Alaika Sugih (Institut Seni Indonesia Denpasar, 2024)
One of Indonesia's growing creative sectors is the Batik industry. The development of the batik industry not only benefits artisans or small and medium-sized enterprises (SMEs) but serves as a creative industry supporting the national economy. This has prompted the government to implement policies to ensure the growth of the batik industry, including promoting innovation and creativity. The author sees opportunities to create contemporary batik in line with these government policies. The term